Cytotoxicity test of 0,78% xanthone from mangosteen pericarp (Garcinia mangostana L.) and 0,2% chlorhexidine gluconate toward BHK-21 fibroblast cells - Afin Aslihatul Ummah; Laksmiari Setyowati; Ketut Suardita (Conservative Dentistry Journal, 2020)
Background. Chlorhexidine gluconate is one of endodontic irrigants that has excellence capability to penetrate into dentin tubules and kill the pathogenic bacteria there. On the other hand, chlorhexidine gluconate has side effects to cause allergic reactions of the tissue and discoloration of the teeth. Xanthone from mangosteen pericarp can be considered as a natural alternative irrigant that usually has a good tolerance to the body. Purpose. The aim of this study compared the cytotoxicity between 0,78% xanthone from mangosteen pericarp and 0,2% chlorhexidine gluconate toward BHK-21 fibroblast cells.  Methods. This study used experimental post-test only control group design. Xanthone from mangosteen pericarp preliminary cytotoxicity tested in various concentrations. Xanthone from mangosteen pericarp classified as a non-toxic concentration at 0,78%. Cytotoxicity of 0,78% xanthone from mangosteen pericarp compare with cytotoxicity of 0,2% chlorhexidine gluconate using MTT assay method. Cytotoxicity of material can be seen from % of cell viability. Viable cell measured by the result of optical density that read by ELISA reader 620 nm. Result. 0,78% xanthone from mangosteen pericarp showed lower cytotoxicity than 0,2% chlorhexidine gluconate toward BHK-21fibroblast cells. One-way ANOVA showed a significant difference between the study groups (P<0,05). Conclusion. 0,78% xanthone from mangosten pericarp showed lower cytotoxicity than 0,2% chlorhexidine gluconate toward BHK-21 fibroblast cells.